1996
DOI: 10.1097/00000441-199606000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Long-Term Management Program for Asthma: Effect on Outcomes in Adult African-Americans

Abstract: To determine if a comprehensive long-term management program, emphasizing inhaled corticosteroids and patient education, would improve outcomes in adult African-American asthmatics a nonrandomized control trial with a 2-year intervention was performed in a university-based clinic. Inclusion criteria consisted of (> or = 5) emergency department (ED) visits or hospitalizations (> or = 2) during the previous 2 years. Intervention patients were volunteers; a comparable control group was identified via chart review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Kelso et al (12) and Kauppinen et al (3) demonstrated a QoL improvement lasting for 2 and 5 years, respectively, after an education program. However, the former study was uncontrolled, and in the latter, the same QoL improvement was observed in the control group, suggesting causes other than the education program were responsible.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Kelso et al (12) and Kauppinen et al (3) demonstrated a QoL improvement lasting for 2 and 5 years, respectively, after an education program. However, the former study was uncontrolled, and in the latter, the same QoL improvement was observed in the control group, suggesting causes other than the education program were responsible.…”
Section: Discussionmentioning
confidence: 96%
“…Although a positive effect on QoL of education programs lasting for up to 1 year of follow-up has often been reported (4,5,12,14), whether the benefit persists in the long term has seldom been investigated (3,12). Kelso et al (12) and Kauppinen et al (3) demonstrated a QoL improvement lasting for 2 and 5 years, respectively, after an education program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not adequately examined by Lieu was the potential for outcome to be influenced by apparent differences in medical practice among specialists and generalists as suggested in several studies. [2][3][4][5] Despite the high level of acuity described among these patients, only 7% of cases and Ͻ5% of controls were identified as having an asthma specialist.…”
Section: Preventing Hospital Admissions For Asthmamentioning
confidence: 99%
“…The specific nature, timing, and dosage of the intervention makes the difference between success and failure, and specialized programs have been demonstrated to be highly successful at implementing effective early intervention measures. [2][3][4][5] Until generalists regard every episode of emergency care and every episode of hospitalization for asthma as a serious treatment failure and either provide intervention measures shown to be effective 6 or refer to an appropriate subspecialty care program for future management, the current endemic nature of asthma emergency care and hospitalization will continue despite the best intention of comprehensive guidelines. 13 Miles Weinberger, MD Pediatric Allergy and Pulmonary Division University of Iowa College of Medicine Iowa City, IA 55242-1083…”
Section: Preventing Hospital Admissions For Asthmamentioning
confidence: 99%